1994
DOI: 10.1093/ajcn/59.2.371
|View full text |Cite
|
Sign up to set email alerts
|

Fat high in stearic acid favorably affects blood lipids and factor VII coagulant activity in comparison with fats high in palmitic acid or high in myristic and lauric acids

Abstract: The effect of fats high in individual, prevalent saturated dietary fatty acids on lipoproteins and hemostatic variables in young healthy subjects was evaluated in a randomized strictly controlled metabolic feeding study. Three experimental diets: shea butter (S; 42% stearic acid), palm oil (P; 43% palmitic palmitic acid), and palm-kernel oil with high-oleic sunflower oil (ML; 10% myristic acid, 30% lauric acid) were served to 15 men for 3 wk each, separated by washout periods. Diet S compared with diet P resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
128
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(142 citation statements)
references
References 29 publications
13
128
0
1
Order By: Relevance
“…Our results agreed with previous work with natural fats and oils (Hegsted et al, 1965;Kris-Etherton et al, 1993;Tholstrup et al, 1994b) in which diets very high in stearic acid ( b 10 en%) produced lower serum concentrations of LDL-C than diets high in 12:0 14:0, 14:0 16:0, or 16:0. Multiple regression analysis of data from investigations of natural fats and oils suggested 14:0 is the most cholesterolemic saturated fatty acid (Hegsted et al, 1965;Mensink & Katan, 1992), but, despite the statistical associations, myristic acid (14:0) is not the major saturated fatty acid in any commonly consumed natural products including butter, meat, and tropical oils (USDA, 1979), and diets high in myristic acid are even higher in lauric or palmitic acid.…”
Section: Effects On Serum Lipoprotein Concentrationssupporting
confidence: 92%
“…Our results agreed with previous work with natural fats and oils (Hegsted et al, 1965;Kris-Etherton et al, 1993;Tholstrup et al, 1994b) in which diets very high in stearic acid ( b 10 en%) produced lower serum concentrations of LDL-C than diets high in 12:0 14:0, 14:0 16:0, or 16:0. Multiple regression analysis of data from investigations of natural fats and oils suggested 14:0 is the most cholesterolemic saturated fatty acid (Hegsted et al, 1965;Mensink & Katan, 1992), but, despite the statistical associations, myristic acid (14:0) is not the major saturated fatty acid in any commonly consumed natural products including butter, meat, and tropical oils (USDA, 1979), and diets high in myristic acid are even higher in lauric or palmitic acid.…”
Section: Effects On Serum Lipoprotein Concentrationssupporting
confidence: 92%
“…This is consistent with the well known reduction of LDL-C concentration with increased UFA. A similar effect is expected for dietary stearic acid because its effects on serum cholesterol fractions are not statistically significantly different to that of oleic acid, it is associated with a reduction in concentration of apoB-100, and it is rapidly converted to oleic acid in the liver where the LDLR gene is expressed (Bonanome and Grundy 1988;Tholstrup et al 1994a;Mensink et al 2003).…”
Section: The Effects Of Fat On Human Blood Lipidsmentioning
confidence: 65%
“…As an example from one of the hardest animal fats, approximately only 27% of tallow from pasture-fed beef is cholesterol-increasing saturated fatty acid (CISFA) (Yang et al 1999b), i.e. chain length of 12-16 carbons, and which would raise serum cholesterol, 1% is polyunsaturated,~4% is conjugated linoleic acid (CLA), and the rest is either MUFA or is the saturated fatty acid (SFA) stearic acid that causes the same effect on total serum cholesterol (TSC) as MUFA (Keys et al 1965;Grande et al 1970;Bonanome and Grundy 1988;Tholstrup et al 1994aTholstrup et al , 1994bde Roos et al 2001;Mensink et al 2003). By comparison, in butter from pasture-fed cows, 42% of the fat is CISFA (Couvreur et al 2006) and would raise serum cholesterol despite butter having a total of more than 60% SFA.…”
Section: Saturated Fat and Cardiovascular Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…26,27 ). In contrast, some studies have shown that stearic acid (18:0) decreases LDL-and increases HDL-cholesterol, which may suggest that it has 28,29 . Also, it has been shown that stearic acid did not increase postprandial inflammation 30 .…”
Section: Saturated Fatty Acidsmentioning
confidence: 91%